Profiling in sepak takraw: physical fitness profile of junior state level sepak takraw players - Akhsan, Nuratiqah Balqis Mohamad (Universiti Sains Malaysia, 2016)
Physical fitness has contribution in a player’s performance. Components of physical fitness are speed, agility, muscular strength, explosive power, flexibility and aerobic fitness. These components are important because sepak takraw skills require high agility, precision, timing and leg strength during spiking and receiving. They need to identify the physical demands and their capacity to respond to those demands to achieve successful performance. Since few studies which analyze physical fitness components have been found, this study was carried out to explore the physical fitness characteristics of state level sepak takraw player. Thirty male sepak takraw payers (age: 14.6±1.25) participated in this study. They represented the state of Pulau Pinang and are currently active state players. The subjects were tested for their anthropometry and fitness components which consist of speed (10m sprint test), flexibility (sit and reach test), agility (T-test), explosive power (vertical jump test), muscular strength (back and leg strength test) and aerobic fitness (beep test). All data were analyzed using one sample T-test. The results stated that the state level sepak takraw players were significantly shorter (155.68±1.75 cm) and lighter (47.45±9.11 kg) compared to the Asean School Game (ASG) player (p<0.05). In addition, they also have a better speed (2.06±0.19 min) and agility (12.27±1.26 min) than the ASG player. No significant difference (p>0.05) was found in flexibility between both groups. Alternatively, ASG player score better results in explosive power (-20.33 kg), muscular strength (-24.77 kg) and aerobic fitness (-20Vo2max)- As a conclusion, the current finding is the ASG player shows better results in explosive power, muscular strength and aerobic fitness compared to the state level players. Meanwhile, state level players show better results in speed and agility. These finding can be used for current players to evaluate their fitness parameters.